Clara cell secretory protein in tracheobronchial aspirates and umbilical cord serum of extremely premature infants with systemic inflammation - Thomas, Wolfgang; Seidenspinner, Silvia; Kawczyńska-Leda, Natalia; Chmielnicka-Kopaczyk, Maria; Marx, Alexander; Wirbelauer, Johannes; Szymankiewicz, Marta; Speer, Christian P. (Neonatology, 2009)
Background: A systemic fetal inflammatory response, reflected by chorioamnionitis with funisitis, is a risk factor for bronchopulmonary dysplasia. Clara cell secretory protein (CC10), a product of pulmonary Clara cells, has anti-inflammatory properties. Local down-regulation of CC10 has been associated with inflammatory lung disease. Increased serum levels of CC10 can indicate injury to alveolar-capillary integrity. Objective: We hypothesized that extremely premature infants with a systemic fetal inflammatory response would have decreased concentrations of CC10 in tracheobronchial aspirates and that CC10 concentrations in umbilical cord serum of these infants would be increased, reflecting alveolar epithelial damage. Methods: We measured CC10 concentrations in tracheobronchial aspirates of 42 ventilated extremely premature infants during their first week of life and in umbilical cord serum of 24 of them by ELISA. Standardized histological examination of the placenta, membranes and umbilical cord was used to identify infants with funisitis. Results: Seventeen infants with funisitis had lower CC10 concentrations in tracheobronchial aspirates on days 1 (p < 0.01) and 3 (p < 0.05) than the remaining 25. Exogenous surfactant treatment was associated with higher CC10 concentrations on day 1 (p < 0.05). Initial leukocyte count correlated inversely with CC10 in tracheobronchial aspirates on days 1-5. Umbilical cord serum concentrations of CC10 did not differ between the infants with funisitis and the controls. Conclusions: Reduced anti-inflammatory CC10 concentrations in airways of extremely premature infants with a fetal inflammatory response might make their lungs susceptible for further postnatal injuries. Umbilical cord serum CC10 is not an indicator for a fetal systemic inflammatory reaction.
Gesehen am 15.11.2023